Catholicism and Civil Society: A Preliminary Comparative Study of Public Engagement by Catholic Churches Across the Four Regions of the Chinese World - HAO, Zhidong (Journal of Research for Christianity in China (JRCC), 2025)
In today’s world, the role of religion in building a robust civil society in a nation has been increas- ingly recognized. More and more scholars are doing research on religion and civil society. In China, too, the study of the relationship between religion and state, and religion and society in general has also been on the rise. But the study of the Catholic Church in civil society building is very much lacking, and a comparative study of the Catholic Church in greater China is even scarcer. This study is an attempt to fill up the gap. In this paper, I intend to illustrate what we know about the relationship between Catholicism and civil society all over the world in gen- eral and in greater China in particular. I will try to explain why some Churches are more active than others in one way or the other. Some of the major factors we consider include structural, cultural, and personal. Finally I ex- plore what our planned project can do in the future in understanding these issues. Such a study will not only help us understand the role of the Catholic Church in civil society building in the four areas of greater China, but help the Church, the state, and the society in general understand how they might coordinate their own policies to- ward one another and together contribute to the building of a civil society.